Use of NFC Technology In Electronic Ticket System For Public Transport (International Journal of Engineering and Computer Science, 2014)
For conducting day to day collaboration, contacts and business transactions, the use of mobile devices are growing. In order to manage their various business and personnel activities, many users are switching on mobile devices.Since the early 1990s, mobile devices have been in use and their wide acceptance may lead them to decrease in use of personal computers everywhere. Powerful new handsets are attracting new customers, that’s why companies and government services are busy in developing seemingly endless mobile applications in the mobile environment. This  innovation will significantly affect the direction and growth of mobile commerce like  Near Field Communication, or NFC, a radio frequency (RF) communication technology that permit data to be exchanged between electronic devices . In payments, coupons, mobile wallet, mobile banking and ticket generation, NFC is expected to be used for